Comparison of Percentage Removal of Petroleum Hydrocarbon on the Effect of Biostimulant in Polluted Soil Environment Using Chromolaena odorata - Victor Chukwuemeka Ukpaka; Abraham Peter Ukpaka; Joy Chukwuemeka Peter Ukpaka; Chukwuemeka Peter Ukpaka (International Journal of Advance in Molecular Engineering, 2024)
The investigation on the comparison of percentage reduction on polluted soil environment using chromolaena odorata as a bio-stimulant upon the effect of contact time revealed increase in percentage removal of total petroleum hydrocarbon (TPH). The rate of total petroleum hydrocarbon (TPH) removal was discovered to have been influenced y the mas of bio-stimulant dosage immersed or introduced into each of the bioreactor. However, as the mass of the bio-stimulant dosage increases the more the percentage reduction also increases in the each of the bioreactor. The rate of TPH reduction in terms of percentage reduction in the control samples was low and this was attributed to lack of available nutrients for the microorganism to makes up as to catalyzed the reaction mechanism of the process for optimum performance of the microbes. Indeed, the research revealed lack of inhibiting effect by the possible inhibiting factors such as pH, temperature, oxygen, contaminants concentration, and other physicochemical parameters. The result contained revealed that the amount of TPH removed by the application of the bio stimulant using sun dried sample is 42.34% for 25g dosage, 61.21% for 50g dosage, 78.37 for 75g dosage and 90.18% for 100g dosage whereas control sample is 10.22% without the application of the bio-stimulant for the period of 42 days sampling. In the case, of room-dried of the bio-stimulant the percentage reduction is 50.49% for 25g dosage, 71.57% for 50g dosage 83.77% for 75g dosage and 98.01% for 100g dosage for contact time of 42days. The research has shown that bio-stimulant subjected into room dried retained their potential nutrients which enhanced bioremediation process as well as facilitate the rate of TPH remediation or degradation of pollutant and indeed, enhanced environmental clean – up of a contaminated soil.
Keywords: Chromolaena odorata; TPH; comparison; effect biostimulant; percentage; reduction